Additions to the decapod crustacean fauna of the Hawaiian Islands, III. A new species of the genus Babamunida (Crustacea: Galatheidae) from Hawaii based on morphological and molecular evidence - Schnabel, Kareen E.; Martin, Joel W.; Moffitt, Robert B. (Zootaxa, 2009)
Babamunida kanaloa n. sp., a new galatheid from approximately 250 m depth off the Northwestern Hawaiian Islands (French Frigate Shoals), is described. DNA sequence data from two gene regions (16S and CO1) corroborates the placement of this new species in the genus Babamunida. Images taken independently using the Deep Submergence Vehicle Pisces IV are almost certainly of the same species based on overall size and color pattern and provide limited ecological information. This new species brings the number of species in the genus Babamunida to six and the total number of galatheid species known from the Hawaiian Islands to four (possibly higher depending on some previous records that might be questionable).